Development and validation of Adaptability to Return-to-Work Scale (ARTWS) for cancer patients - Guo, Yu-Jie; Xue, Ping; Gu, Wen-wen; Su, Xiao-qin; Li, Jia-mei; Kuai, Ben-xin; Xu, Jia-shuo; Xie, Hui-wen; Han, Ping-ping (Frontiers in Psychology, 2024)
The research on cancer patients returning to work in China is still in its infancy, and there is no research and discussion on the adaptability to return-to-work for cancer patients. It is critical to develop the adaptability to return-to-work scale (ARTWS) for cancer patients and evaluate its psychometric properties. In stage 1, the items of the initial scale were compiled based on the theoretical model and literature review results.Then, through two rounds of Delphi expert consultation (N=15) and a pilot survey ( N=40 ), the initial scale was further checked and revised. In stage 2, Three hundred seventy-six patients were included, and the construct validity and reliability of the ARTWS were assessed by confirmatory factor analysis (CFA) and exploratory factor analysis (EFA). The final ARTWS consisted of 24 items. "Focusing on rehabilitation", "Rebuilding Self-efficiency", and "Adjusting plans" as common factors in determining adaptability to return to work for cancer patients, and the cumulative variance contribution rate for these three factors was 66.6%. The S-CVI of the total scale was 0.979. The Cronbach's α coefficient was 0.937 and the 2-week test-retest reliability was 0.814. ARTWS has good correlation validity.